(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
The concept of fractional calculus dates back to the early days of calculus and may be traced back to Arbogast’s publications in the 1800s. Multiple derivatives are defined in this situation by powers of D that are logically discovered to be integral in nature. However, this gave birth to the idea of evaluating this operator’s fractional power and attempting to determine its equivalent form or operating it on some function in a meaningful way.This part of calculus is classified as special calculus, and it did not find much application in engineering until the advent of electronic computers and control systems, where it began to show its capability, such as increasing the number of control parameters in a PID control system, which essentially increases its ability to be optimised, albeit at a higher complexity. This project begins with introducing the fundamentals of fractional calculus, followed by fractional derivatives of standard functions and their interpretation, and then provides fractional calculus applications in the context of electronics.